Batas Kewenangan Ahli Madya Optometri dan Perawat Kesehatan Mata Paska Berlakunya Undang Undang Kesehatan Nomor 17 Tahun 2023 - YV Agung Riono; James Davidta Ginting (Verdict: Journal of Law Science, 2026)
The enactment of Indonesia’s Health Law No. 17 of 2023 has fundamentally restructured the legal framework governing health professionals, including optometrists and ophthalmic nurses. However, the transition from sectoral legislation to this omnibus law has created normative ambiguities regarding the distribution of professional authority. This study aims to analyze normative conflicts and legal gaps concerning the classification and scope of practice of optometrists and ophthalmic nurses under the Health Law No. 17/2023, the National Education System Law No. 20/2003, the Higher Education Law No. 12/2012, and the Civil Service Law No. 20/2023, while proposing regulatory harmonization. This study employs a normative juridical method using statutory, conceptual, and comparative approaches. Relevant legislation, implementing regulations, and Scopus-indexed journals (2020–2025) were analyzed through systematic legal interpretation. The findings reveal three major normative conflicts: the inconsistency between educational qualifications and professional competencies of optometrists; overlapping authority regarding refractive examinations and job classifications of ophthalmic nurses; and conflicting competency standards established by the Ministries of Health and Education. The study also identifies legal gaps concerning specialist nursing practice, independent practice regulations for allied health professionals, and collaborative protocols in primary eye care. These issues require regulatory harmonization through coordinated ministerial regulations, implementing guidelines, and standardized collaborative protocols to ensure legal certainty, improve service efficiency, and strengthen patient safety within Indonesia’s eye care system.